EXPERIENCE-ORIENTED MODEL OF BUDGET ALLOCATION AND COST CONTROL FOR ENGINEERING CONSULTING PROJECTS - Wang, Shih Hsu; Chang, Shu-Pin; Wang, Wei-Chih (International Journal of Industrial Engineering: Theory, Applications and Practice, 2023)
This paper presents an experience-oriented model of budget allocation and cost control for engineering consulting projects. The proposed model comprised two modules: a work item module and a work duration module. Regarding the work item module, a project manager employed the analytic hierarchy process (AHP) to determine the budget percentage allocated to each work item. Regarding the work duration module, this study compiled all S-curves appearing in each budget percentage range in past projects. A project manager then selected the optimal curve shape for each work item to determine the daily budget allocation and cost control limits throughout the work duration of each work item. Testing revealed that the proposed model facilitates project managers’ budget allocation decision-making, determines budget control limits for the overall project and for each work item and identifies work items that may be out of control at an early stage.